A Shift And Equivalence Translation Analysis On The English - Indonesian Subtitling Of The Amazing Spiderman 4 Movie - Ambarsih, Riris; , Dra, Dwi Haryanti, M.Hum; , Siti Fatimah, SPd, M. Hum (2013)
This is descriptive research. It aims at describing translation shift verbs and verb phrase, and to describe translation shift verbs and verb phrase found on The Amazing Spiderman movie which is translated into Indonesian. In collecting data, the writer uses documentation by coding and selecting English sentences containing verb and verb phrases in The Amazing Spiderman 4 Movie scripts. From the data analysis, the researcher finds two translation shifts, namely: category shift and level shift. From 151 data the researcher finds 5 shifts which belongs to category shift, (1) verb that is translated into noun 1 data or 1%, (2) verb that is translated into adverb 2 data or 1%, (3) verb that is translated into adjective 1 data or 1%, (4) linking verb that is translated into adverb 10 data or 7%, and (5) verb that is translated into verb imperative 5 data or 3%. There are 7 translation shifts which belongs to level shifts. There are 132 data, (1) verb that is translated into verb phrase 11 data or 5%, (2) verb translated into verb add 3 data or 2%, (3) verb that is phrase translated into verb 101 data or 66%, (4) verb phrase that is translated into noun 1 data or 1%, (5) verb phrase that is translated into adverb 8 data or 5%, (6) verb phrase that is translated into verb imperative 7 data or 5%, and (7) verb phrase that is translated into verb add 1 data 1%. The second result is equivalence translation. From 151 data the researcher divided them into equivalence and non equivalence translation. (1) The equivalence translation is 150 data or 99% and (2) non equivalence translation is 1 data or 1%.